Arctic Report Card Underscores Continued Long‐Term Warming Trend. (24th December 2013) - Showstack, Randy
Abstract : Although fewer record‐setting snow and ice events occurred in the Arctic in 2013 compared to 2012, "the impacts of the persistent warming trend of over 30 years remain clearly evident, " according to the 2013 Arctic Report Card issued by the U.S. National Oceanic and Atmospheric Administration (NOAA) at a 12 December news briefing at the AGU Fall Meeting in San Francisco, Calif.